Photography and its shadow - Kenaan, Hagi (Stanford University Press, 2020)
"By looking at photographic practices and photographs from the origins of photography to today's selfies, Snapchat, and Google Street View, this book offers a fresh philosophical understanding of how photography has become an intrinsic condition of the human"-- Provided by publisher
Keywords: Photography -- Psychological aspects.; Photographie -- Aspect psychologique.; ART -- Criticism.; Photography -- Psychological aspects